Labor market power, self-employment, and development - Francesco Amodio; Pamela Medina; Monica Morlacco (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
This paper shows that self-employment shapes labor market power in low-income countries, affecting industrial development. Using Peruvian data, we show that wage-setting power increases with concentration, but less so where self-employment is more prevalent. A general equilibrium model shows that while concentration increases oligopsony power, it also raises labor supply elasticity by pushing workers into self-employment, thereby mitigating labor market power. Conversely, pro-competitive policies that draw workers into salaried jobs may increase labor market power, with limited overall impact. We demonstrate that these policies are only effective if they tackle labor market power.
Keywords: J2; J3; J42; L10; O14; O54; 330; labor market power; monopsony; self-employment; sorting; development